Extraction and analysis of signatures from the Gene Expression Omnibus by the crowd - Zichen Wang (Nature Portfolio, 2016)
A wealth of gene expression data is publicly available, yet is little use without additional human curation. Ma’ayan and colleagues report a crowdsourcing project involving over 70 participants to annotate and analyse thousands of human disease-related gene expression datasets.